IL‐17 regulates DC migration to the peribronchial LNs and allergen presentation in experimental allergic asthma. Issue 7 (29th March 2020) - Jirmo, Adan Chari; Busse, Mandy; Happle, Christine; Skuljec, Jelena; Dalüge, Kathleen; Habener, Anika; Grychtol, Ruth; DeLuca, David S.; Breiholz, Oliver D.; Prinz, Immo; Hansen, Gesine
Abstract: IL‐17 is associated with different phenotypes of asthma, however, it is not fully elucidated how it influences induction and maintenance of asthma and allergy. In order to determine the role of IL‐17 in development of allergic asthma, we used IL‐17A/F double KO (IL‐17A/F KO) and WT mice with or without neutralization of IL‐17 in an experimental allergic asthma model and analyzed airway hyperresponsiveness, lung inflammation, T helper cell polarization, and DCs influx and activation. We report that the absence of IL‐17 reduced influx of DCs into lungs and lung draining LNs. Compared to WT mice, IL‐17A/F KO mice or WT mice after neutralization of IL‐17A showed reduced airway hyperresponsiveness, eosinophilia, mucus hypersecretion, and IgE levels. DCs from draining LNs of allergen‐challenged IL‐17A/F KO mice showed a reduction in expression of migratory and costimulatory molecules CCR7, CCR2, MHC‐II, and CD40 compared to WT DCs. Moreover, in vivo stimulation of adoptively transferred antigen‐specific cells was attenuated in lung‐draining LNs in the absence of IL‐17. Thus, we report that IL‐17 enhances airway DC activation, migration, and function. Consequently, lack of IL‐17 leads to reduced antigen‐specific T cell priming and impaired development of experimental allergic asthma. Abstract : Cellular mechanisms influenced by IL‐17 are yet to be fully elucidated. Here, we show that the presence of IL‐17 enhances antigen uptake and in vivo activation of DCs and their migration to the draining LNs in an experimental model of allergic asthma.